Homozygous variants in SYCP2L cause premature ovarian insufficiency. Issue 3 (17th April 2020) - He, Wen-Bin; Tan, Chen; Zhang, Ya-Xin; Meng, Lan-Lan; Gong, Fei; Lu, Guang-Xiu; Lin, Ge; Du, Juan; Tan, Yue-Qiu
Abstract : Background: The genetic causes of the majority of cases of female infertility caused by premature ovarian insufficiency (POI) are unknown. Objective: To identify the genetic causes of POI in 110 patients. Methods: Whole-exome sequencing was performed on 110 patients with POI, and putative disease-causative variants were validated by Sanger sequencing. Bioinformatic and in vitro functional analyses were performed for functional characterisation of the identified candidate disease-causative variants. Results: We identified two homozygous variants (NM_001040274: c.150_151del (p.Ser52Profs*7), c.999A>G (p.Ile333Met)) in SYCP2L in two patients, which had co-segregated with POI in these families. Bioinformatic analysis predicted that the two variants are deleterious, and in vitro functional analysis showed that mutant SYCP2L proteins exhibited mislocalisation and loss of function. Conclusions: SYCP2L is a novel gene found to be responsible for human POI. Our findings provide a potential molecular marker for POI and improve the understanding of the genetic basis of female infertility.